Realização social da natureza pelo turismo na Chapada dos Veadeiros - Everaldo Batista da Costa; Maria Geralda de Almeida; Rafael Fabrício de Oliveira; Rúbia de Paula Rúbio (Confins)
Situated in the Brazilian State of Goiás, the National Park Chapada dos Veadeiros has been singularized due to its landscape, which comprises elements of physiographic and cultural values. Such forged singularity attracts, annually, thousands of tourists seeking consecrated attractions. The attractiveness of this highly preserved redoubt of the Brazilian Savanna biome (cerrado) increases with its inclusion on the UNESCO World Heritage List, which makes tourism (as a modern productive activity) one of the most important sources of income for the different groups dwelling in the region. Thus, through the performance of fieldworks to compose a primary data base, as well as documental and bibliographic resources, this article presents an ample and current overview on the logic of tourism and on the main socio-spatial relationships it promotes at the National Park Chapada dos Veadeiros, which integrates the municipio of Alto Paraíso de Goiás and the village of São Jorge.